Effect of Catechins Uncaria gambir Roxb. on Blood Sugar Levels of Mus musculus L. Hyperglycemia - Elsa Yuniarti; Sari Ramadhani (Jurnal Penelitian Pendidikan IPA, 2023)
Sugar is one of the main energies for the body, but do not consume it in excess, because it causes blood sugar levels to increase, this condition is called hyperglycemia. Gambir contains beneficial antioxidants such as catechins. Catechins are polyphenolic compounds belonging to the flavonoid group. The purpose of this study was to determine the effect of gambier catechins on blood sugar levels in hyperglycemic mice. This study is an experimental study with a completely randomized design using 25 samples of male mice for 42 days with two control groups and three treatment groups, namely the negative control was not treated, and the positive control was given glibenclamide after sucrose induction, P1, P2, and P3 were taken with catechins different concentrations after sucrose induction. Checking blood sugar levels using a glucometer (Easy Touch). Data were analyzed by one-way of variance (ANOVA) followed by a DMRT follow-up test at a 5% level. The results showed that gambier catechins had an effect (p<0.05) on blood sugar levels in hyperglycemic mice. The most effective gambier catechin administration was at P2 (80% catechin concentration).